Formulasi sediaan pewarna pipi menggunakan pewarna alami kopigmentasi biji kesumba keling (Bixa orellana L.) dengan angkak merah - Salman Salman; Sudewi; Aprilia Ulfa; Rahma Yulia; Meutia Indriana (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; annatto (Bixa orellana L.) is a plant planted in the house or roadside gardens, containing alkaloids, flavonoids, and carotenoids. Red yeast rice is a natural product from China, resulting from traditional fermentation. This study aims to determine the co-pigmentation of annatto and red yeast rice seeds in the form of ethanol extract, which can be formulated as a natural dye into blush on preparations that, at specific concentrations, produce natural colors that meet the requirements and do not cause skin irritation. Methods; the study used an experimental approach using the test material of annatto seeds (Bixa orellana L.) and red yeast rice. The study was initiated by sampling, plant identification, Simplicia processing, and co-pigmentation of annatto (Bixa orellana L.) and red yeast rice seeds by maceration using 96% ethanol extract, p; phytochemical screening was carried out. The basic modified formulation of blush on a ratio of 1:2 between annatto seeds and red yeast rice seeds was made in 3 preparations with a concentration of 3%, 6%, and 9%, and blank. Examination of the physical quality of the preparation includes color dispersion test (homogeneity), polish test, stability test, and irritation test. Result; the results of the study concluded that the copigmentation of annatto (Bixa orellana L.) seeds and red yeast rice in the form of ethanol extract could be formulated into blush on preparations as natural dyes, which are homogeneous, easy to apply,y and stable for 12 days of storage. Produces different colors depending on the concentration contained in the preparation of the cheek dye. The co-pigmented cheek dyes made from ethanol extract of annatto (Bixa orellana L.) and red yeast rice seeds were non- irritating to the skin.